New design procedure for stability of soft clays / by Charles C. Ladd, Roger Foott. - Massachusetts Institute of Technology. Department of Civil Engineering.; Foott, Roger, 1946-; American Society of Civil Engineers. Soil Mechanics and Foundations Division.; Ladd, Charles C. (Charles Cushing) (Tufts University. Tisch Library., 2019)
1 online resource (32 leaves, 10 unnumbered leaves of plates) : illustrations; "Paper submitted to the Soil Mechanics and Foundations Division of ASCE.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.